Happiness and pleasure: a dialogue between Epicurus and Skinner - Tamura, Thais Tiemi; Laurenti, Carolina (Perspectivas em Análise do Comportamento, 2017)
The discussion concerning happiness and pleasure occupied a central role in the philosophy of Epicurus. According to the philosopher, pleasure is the beginning and the end of a happy life. B. F. Skinner also elaborated on the issue of happiness and pleasure. However, he argues that even with plenty of pleasant events in Western society, people are unhappy. Despite these and other differences, this article discusses some points of proximity between the philosophies of Epicurus and Skinner. us, it shows not only that Epicurean philosophy could clarify the radical behaviorist’s idea of happiness, but it also sheds light on the contemporary challenge of reconciling the enjoyment of life and the survival of cultures.